Sosialisasi Pendokumentasian Asuhan Keperawatan Berbasis SDKI, SLKI dan SIKI di RS Sansani Pekanbaru - Mayenti, Fitra; Meri, Dilgu; Maria, Lisda (Jurnal Abdimas Kesehatan (JAK), 2024)
Nursing care is a scientific method of nursing in developing the body of nursing science. Nursing care is a means of developing nursing discipline and nursing practice which the characteristics of nursing and differentiate the nursing profession from other professions. This development can be carried out continuously through nursing research. Standard nursing language is one of the nursing innovations that is continuously carried out to develop the body of nursing knowledge and the quality of nursing care. The SDKI is a diagnostic standard that can be used in nursing clinical decision making based on ease of use, clarity of diagnostic reasoning and completeness of the types of diagnoses available as well as language standards. SIKI is all treatment carried out by nurses which is based on knowledge and clinical judgment to achieve outcomes. SLKI is the final result of nursing intervention which consists of indicators or criteria for problem recovery results. This community service method is in the form of lectures, namely socializing documentation of nursing care based on SDKI, SLKI and SIKI to inpatient nurses at Sansani Hospital Pekanbaru. Community service results for 20 participants consisting of room nurses and students of the Al Insyirah Institute of Health and Technology, showed that the percentage of participants' knowledge before (pretest) they were given material on documenting nursing care based on SDKI, SIKI at Sansani Hospital Pekanbaru was 80%, and after (posttest) they were given material, participants' knowledge increased to 100%. There was an increase in the knowledge of implementing nurses before and after providing material for documenting nursing care based on SDKI, SLKI and SIKI at Sansani Hospital